Vertically transmitted symbionts as mechanisms of transgenerational effects - Gundel, Pedro Emilio (2017)
PREMISE OF THE STUDY: A transgenerational effect occurs when a biotic or abiotic environmental factor acts on a parental individual and thereby affects the phenotype of progeny. Due to the importance of transgenerational effects for understanding plant ecology and evolution, their underlying mechanisms are of general interest. Here, we introduce the concept that inherited symbiotic microorganisms could act as mechanisms of transgenerational effects in plants. METHODS: We define the criteria required to demonstrate that transgenerational effects are microbially mediated and review evidence from the wellstudied, vertically transmitted plant–fungal symbiosis (grass– Epichloë spp.) in support of such effects. We also propose a basic experimental design to test for the presence of adaptive transgenerational effects mediated by plant symbionts. KEY RESULTS: An increasingly large body of literature shows that vertically transmitted microorganisms are common in plants, with potential to affect the phenotypes and fitness of progeny. Transgenerational effects could occur via parental modification of symbiont presence/absence, symbiont load, symbiont products, symbiont genotype or species composition, or symbiont priming. Several of these mechanisms appear likely in the grass– Epichloë endophytic symbiosis, as there is variation in the proportion of the progeny that carries the fungus, as well as variation in concentrations of mycelia and secondary compounds (alkaloids and osmolytes) in the seed. CONCLUSIONS: Symbiont-mediated transgenerational effects could be common in plants and could play large roles in plant adaptation to changing environments, but definitive tests are needed. We hope our contribution will spark new lines of research on the transgenerational effects of vertically transmitted symbionts in plants.